Seven new species of the Neotropical electric fish Gymnotus (Teleostei, Gymnotiformes) with a redescription of G. carapo (Linnaeus) - Albert, James S.; Crampton, William G.r. (Zootaxa, 2003)
Seven new species of Gymnotus are described, and a redescription of the type species G. carapo sensu-stricto Linnaeus (G. carapo s.s.) is provided, from examination of populations from throughout tropical South and Middle America. The new species are described on the basis of unique combinations of characters. Five of the new species are members of the G. carapo species-group: 1, Gymnotus choco n. sp., from the Baudó and Atrato basins on the Pacific and Caribbean slopes of Colombia; 2, Gymnotus esmeraldas n. sp., from the Esmeraldas and Guayaquil basins on the Pacific Slope of Ecuador; 3, Gymnotus henni n. sp., from the Calima and Juradó basins on the Pacific Slope of Colombia; 4, Gymnotus paraguensis n. sp., from the Paraguay basin; 5, Gymnotustigre n. sp., from the Amazon basin of Ecuador, Peru and Brazil. Two of the new species are members of the G. pantherinus species-group: 1, Gymnotus javari n. sp., from the Amazon, Napo, Javarí, and Ucayali basins; 2, Gymnotus panamensis n. sp., from Atlantic slope of western Panama. Gymnotus carapo s.s. is restricted to the Amazon and Orinoco basins, the Island of Trinidad, the coastal basins of the Guianas, and the Brazilian state of Piauí. Six allopatric populations of G. carapo s.s are recognized from differences in the mean, modal or median values of morphometric and meristic traits: 1, Eastern Amazon; 2, Parnaíba and Itapicuru basins; 3, Branco basin; 4; Guiana Shield, Orinoco basin and Island of Trinidad; 5, Madeira basin of Brazil, Bolivia and Peru; 6, Western Amazon basin of Brazil, Colombia, Ecuador, and Peru. Four of the new species representing both the G. carapo and G. pantherinus species-groups inhabit waters to the west of the Andean Cordillera. The biogeographic distributions of these species-groups suggest origins and early diversification before the most recent Andean orogeny, c. 8–12 mya.